Development A Spinning Wheel Learning Media To Teach Writing Skill For Tenth Grade Of SMK Hidayatul Mubtadiin Kanigoro: English - Dewinka Intan Milani Kusuma Anjani Junariyah; Siti Rofi'ah; Ahmad saifudin (Prodi Tadris Bahasa Inggris, 2023)
Abstract This study aims to develop Spinning wheel media to teach narrative text writing skills. Based on the results of interviews with English teachers and students who are lacking in writing. Researchers used the Borg and Gall R&D model in Sugiono's book, researchers only used 7 of the 10 steps of Borg and Gall, namely: Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial and Product Revision.The purpose of this research is to develop the use of spinning wheel game learning media in the teaching and learning proces students who need the ability to write English, and the differencess with the previous researcher are the purpose of the study. This research was conducted in SMK Hidayatul Mubtadiin Kanigoro at Tenth Grade which had 27 students, 13 famales 14 male. The study was successful with a student satisfaction response rise of 87% which can be said to be Very Valid.